Financing the 2000 Election - Magleby, David B. (Book collections on Project MUSE., 2002)
A series of 10 papers, presented by Magleby (Center for the Study of Elections and Democracy, Brigham Young U.), explore the money issues behind the American political campaigns of 2000. Patterns of campaign spending, strategies of funding campaigns, patterns of change across different political organizations, and other broad issues are discussed in early chapters, while later contributions delve into the particulars of the financing of the presidential nominations, the general presidential election, the spending of interest groups, and congressional campaigns. The material focuses on the Republicans and the Democrats, although there is some very brief discussion of the campaigns of Pat Buchanan, Ralph Nader, and other third party candidates. Annotation copyrighted by Book News, Inc., Portland, OR.